2018
DOI: 10.1016/j.jss.2017.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors for increased resource utilization in kidney transplantation

Abstract: Medicaid insurance, self-rated poor health status, and errors in the medication regimen or monitoring were significant risk factors for increased health care utilization in kidney transplant recipients. Further research is warranted to validate these potential risk factors, determine the long-term impact on graft/patient survival, and assess the mutability of these risks through prospective identification and intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Medication errors and medication safety are major issues in transplant recipients, as the majority are receiving more than 10 medications and 20 doses per day; these agents are known to have substantial toxicities and numerous drug interactions. Nonadherence, adverse drug events, and errors can have a major influence on clinical outcomes after transplant . The results of this study demonstrated reduced medication errors (mainly in discrepancies within the electronic medical record) and improved patient‐reported adherence, with low rates of newly reported adverse drug events.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Medication errors and medication safety are major issues in transplant recipients, as the majority are receiving more than 10 medications and 20 doses per day; these agents are known to have substantial toxicities and numerous drug interactions. Nonadherence, adverse drug events, and errors can have a major influence on clinical outcomes after transplant . The results of this study demonstrated reduced medication errors (mainly in discrepancies within the electronic medical record) and improved patient‐reported adherence, with low rates of newly reported adverse drug events.…”
Section: Discussionmentioning
confidence: 63%
“…Nonadherence, adverse drug events, and errors can have a major influence on clinical outcomes after transplant. [37][38][39][40] The results of this study demonstrated reduced medication errors (mainly in discrepancies within the electronic medical record) and improved patient-reported adherence, with low rates of newly reported adverse drug events. These findings offer promise that educational and technology interventions, driven by transplant pharmacists, may improve medication-related outcomes.…”
Section: Discussionmentioning
confidence: 66%
“…Thirty-seven studies (46%) were conducted utilising data from a single centre, 28 (35%) utilised data from a national database, 11 (14%) used data from multiple centres while the remaining 5 (6%) focused on provincial data. Other than database review or medical chart abstraction, five studies included patient surveys (Flythe et al, 2017;Jasinski et al, 2018;Shi et al, 2018;Vranian et al, 2018;Wjayantii et al, 2019). Prevalence of readmission is summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Medication-related problems are common among kidney transplant recipients. The continued management of comorbidities, a substantial new medication regimen (eight drugs per day, on average) and intensive follow-up care constitute a significant challenge for these patients 2 3. After transplantation, medication discrepancies can lead to fluctuating levels of immunosuppression, which in turn may result in transplant rejection, infection, and/or drug toxicity 4.…”
Section: Introductionmentioning
confidence: 99%